The influence of high-energy ball milling on the heterogeneous reaction kinetics in the Ti-Si system. (February 2018) - Nepapushev, A.A.; Rogachev, A.S.; Mukasyan, A.S.
Abstract: The high-temperature (1300–1600 K) kinetics for the Ti-Si reactive system were investigated using electro-thermal analysis. The influence of short-term (1–3 min) high-energy ball milling (HEBM) of Ti+0.6Si heterogeneous powder mixtures on the kinetic parameters was also studied. It was shown that HEBM leads to a significant decrease of the apparent activation energy (Ea ) of the solid-state reaction between silicon and titanium. For the non-milled mixture, Ea is 339 ± 63 kJ/mol, while after 3 min of HEBM it drops more than twice to 148 ± 12 kJ/mol. The reaction initiation temperature also decreases with an increase of HEBM time: from 1467 ± 62 K for the pristine mixture to 1110 ± 42 K after 3 min of mechanical treatment. The conclusion was made that a decrease of crystalline size and an increase of the crystal lattice defect concentration, which in combination enhance the grain boundary diffusion, can be responsible for the high reactivity of the mechanically activated mixtures. Highlights: The reaction kinetics in the Ti-Si system. The reaction activation energy depends on the duration of high-energy ball milling. A lower ignition temperature corresponds to a lower activation energy. High-energy ball milling allows for controlling the reactivity of the system.